Molar Refraction and Polarizability of Antiemetic drug 4-amino-5-chloro-N-(2-(diethylamino)ethyl)-2 methoxybenzamide hydrochloride monohydrate in Aqueous-Sodium or Lithium Chloride Solutions at 30 °C - Rajendrakumar T. Sawale,Tukaram M. Kalyankar,Roy George,Santosh D. Deosarkar (Journal of Applied Pharmaceutical Science, 2016)
The 4-amino-5-chloro-N-(2-(diethylamino)ethyl)-2 methoxybenzamide hydrochloride monohydrate exhibits antiemetic and parasympathomimetic activity. Density (ρ) and refractive index (nD) measurements were carried out as a function of drug concentration (c=0.01-0.11 mol•L-1) in aqueous NaCl/LiCl (c=0.05, 0.10 and 0.15 mol•L-1) solutions at 30 °C. Linear relation of concentration dependence of density and refractive index were studied. Molar refractivity (Rm) of solution was calculated from density and refractive index data and polarizability (α) was calculated from molar refractivity data. Stronger polarizability effects have been observed with increase in drug concentration.
Keywords: Density,Physicochemical properties,Molecular interactions,Polarizability.